Failure of immunological competence: when to suspect? - Fernanda Pinto-Mariz (Elsevier, 2021)
Objectives: To draw physicians' attention to the different warning signs of diseases of inborn errors of immunity. Data sources: A non-systematic review of the literature was carried out in the PubMed, LILACS, and SciELO databases, in addition to consultation of reference textbooks. Summary of the findings: It is known that the lack of immunological competence observed in patients with inborn errors of immunity diseases causes particularly serious and/or recurrent infections. However, manifestations related to autoimmunity, inflammation, allergies, and malignancy can also occur. Aiming at the early identification of these patients, a list of warning signs for inborn errors of immunity was created, in which the need for intravenous antibiotics or prolonged antibiotics use to control infection, failure to thrive, and positive family history for this group of diseases are considered the most sensitive. Regarding non-infectious manifestations, early onset, difficulty in controlling with the usual treatments, atypical presentations or association with other warning signs are noteworthy, and investigation for inborn errors of immunity in these situations is recommended. Conclusions: This article highlights the importance of considering this group of diseases even in the face of patients with non-infectious manifestations. Disclosure of inborn errors of immunity diseases, especially to non-specialists, is essential for early diagnosis and, consequently, for the reduction of these patients' morbidity and mortality.